2022
DOI: 10.3390/ma15186204
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Na0.5Bi0.5TiO3 Ceramics Modified with Fe and Mn

Abstract: Na0.5Bi0.5TiO3 (NBT) and Fe- and Mn-modified NBT (0.5 and 1 mol%) ceramics were synthesized by the solid-state reaction method. The crystal structure, dielectric and thermal properties of these ceramics were measured in both unpoled and poled states. Neither the addition of iron/manganese to NBT nor poling changed the average crystal structure of the material; however, changes were observed in the short-range scale. The changes in shapes of the Bragg peaks and in their 2Θ-position and changes in the Raman spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Manganese doping is widely acknowledged as an effective method for ameliorating the detrimental effects of element volatilization in NBT-based films [12][13][14]. For instance, it has been demonstrated that Mn-doped NBT films have leakage current densities up to four orders of magnitude lower than those observed in pure NBT films [12].…”
Section: Introductionmentioning
confidence: 99%
“…Manganese doping is widely acknowledged as an effective method for ameliorating the detrimental effects of element volatilization in NBT-based films [12][13][14]. For instance, it has been demonstrated that Mn-doped NBT films have leakage current densities up to four orders of magnitude lower than those observed in pure NBT films [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, well-known ceramic materials with functional properties, e.g., [ 1 , 2 , 3 , 4 , 5 , 6 ], have constituted various engineering materials with versatile applications in modern microelectronics [ 7 , 8 ]. These materials include multiferroic composite materials obtained based on ferroelectric and magnetic compounds [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%